The Stefan problem - Borodin, M.A. (Інститут прикладної математики і механіки НАН України, 2008)
The Stefan problem in its classical statement is a mathematical model of the process of propagation of heat in a medium with di erent phase states, e.g., in a medium with liquid and solid phases.The process of propagation of heat in each phase is described by the parabolic equations. In this work we prove the existence of the global classical solution in a two-phase multidimensional Stefan problem. We apply a method which consists of the following. First, we construct approximating problems, then we prove some uniform estimates and pass to the limit.